Faktor-Faktor Yang Mempengaruhi Volume Ekspor Teh PTPN IX, Jawa Tengah - Agnes Chaprilia; Yuliawati Yuliawati (Universitas Sebelas Maret, 2018)
The purpose of this reasearch is to 1) analyze the factors that influence tea export volume of PTPN IX, 2) to know the overview of PTPN IX tea export trend and forecasting. The kind of this research is quantitative descriptive and use secondary data that sourced from related agencies and organizations. Data in form time series during 96 months from January 2010 until December 2017 are used in this research. This research use multiple linear regression and ARIMA (Box-Jenkin) as analysis technique. Regression analysis result show tea export price, coffee price, and exchange rate had a negative effect and significant for export volume with value R2 is 0,479. Trend analysis use ARIMA shown period of tea export volume from January 2010 until December 2017 had fluctuated and shown a downward trend.